Answer:
no idea
Step-by-step explanation:
Answer:
Exponential transformation.
Step-by-step explanation:
y = log_3 (x + 3) - 2
To transform this into exponential, we have:
Adding 2 to both sides
y + 2 = log_3 (x + 3)
3^(y + 2) = x + 3
x = 3^(y + 2) - 3
Answer:
2 should be distributed as 2y + 8; y = 4
Step-by-step explanation:
2(y + 4) = 4y
Distribute
2y + 8 = 4y
Step 2 is incorrect because the added instead of multiplied
Continuing on to correct the problem
Subtract 2y from each side
2y+8-2y = 4y-2y
8 = 2y
Divide by 2
8/2 = 2y/2
4 =y
Answer:
1 1/2
Step-by-step explanation:
SO first convert into mixed
1 15/30
Now simplify
1 1/2
IF YOU DONT WANT MIX AND LEAVE AS IMPROPER
3/2
Answer:
4xp-9
Step-by-step explanation: